Investigations for Soil Contamination with Hydrocarbon Compounds near Oil Stations - Khaleel, Zahraa A.; Shaban, Auday H.; Al Maliki, Ali A. (Journal of physics. Conference series, 2024)
Field companies are subject to many standards to preserve the environment. Oil companies are considered among the companies that cause the most environmental pollution for two reasons: the first is the extraction of large quantities of crude oil, and the second is their violation of the controls imposed on them. In this research the investigations on the nearby and around a Rumaila oil station area were abducted scientifically through a real tested sample. In this research, investigations in an area near and around the Rumaila Oil Station were conducted scientifically through real laboratory samples. An analysis was made to determine the total petroleum hydrocarbons (TPH), where 22 samples were collected, as well as 5 laboratory samples of soil from an unpolluted area, and crude oil was added to it in known proportions to determine the spectral signature. The ASD Field spec 3 device was used to record the spectral signatures of each sample. Areas sensitive to hydrocarbons 17050 and 1350 appeared. The results show a variation in the concentrations of hydrocarbon in the samples from (2 ppm) at the minimum and reach (197 ppm) at other locations around the station.